Peers or Police? Detection and Sanctions in the Provision of Public Goods - Gregory DeAngelo; Laura Katherine Gee (Institute of Labor Economics (IZA), 2018)
Sanctions are a common method to discourage free-riding in the provision of public goods. However, we can usually only sanction those who are detected performing the bad act of free-riding. There has been considerable research on the type of sanctions imposed, but this research almost always automatically detects everyone's actions and broadcasts them to the group. This is akin to assuming that a group always has a police force or motivated peer reporting to detect and announce the actions of bad actors. However, in many situations bad acts go undetected and unknown to others. We use a lab experiment to compare public good contribution decisions in an environment where we relax the assumption that detection is automated. The common result that sanctions and the likelihood of detection share an inverse relationship continues to be found in our results. However, free-riders are unwilling to pay for detection when sanctioning is conducted at the group level, because a criminal does not want to fund the police who will catch his bad acts. But, when detection is conducted among peers, free-riders are willing to pay to detect other individuals that free-ride.
Keywords: C72; C91; C92; D7; H41; 330; public goods; punishment; detection; deterrence